Peasant-managed Agricultural Growth in China: Mechanisms of Labour-driven Intensification - van der Ploeg, Jan Douwe; Ye, Jingzhong; Wu, Huifang; Wang, Chunyu (The International Journal of Sociology of Agriculture and Food, 2014)
This article discusses the different mechanisms that sustain labour-driven intensification in contemporary Chinese agriculture. They include: labour investments directed at improving resources; the intensification of cropping schemes; fine-tuning production processes, resulting in yield increases; embedded specialization; the reorganization of space; and on-farm processing, which gives more value-added per unit of end product. These mechanisms help to enlarge the autonomy of peasant families and their units of production. They simultaneously help to improve incomes. The article pays special attention to migrant labour and the way it helps to enlarge investments and spur the intensification of agricultural production.